2010
DOI: 10.1523/jneurosci.1683-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Controls Cannabinoid CB1 Receptor Function in the Striatum

Abstract: The role of brain-derived neurotrophic factor (BDNF) in emotional processes suggests an interaction with the endocannabinoid system. Here, we addressed the functional interplay between BDNF and cannabinoid CB 1 receptors (CB 1 Rs) in the striatum, a brain area in which both BDNF and CB 1 s play a role in the emotional consequences of stress and of rewarding experiences.BDNF potently inhibited CB 1 R function in the striatum, through a mechanism mediated by altered cholesterol metabolism and membrane lipid raft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 74 publications
6
56
0
1
Order By: Relevance
“…Previous studies have shown that cannabis use can alter levels of BDNF in humans as well as in animals (Jockers-Scherübl et al 2004;Butovsky et al 2005). Recently, it was reported that BDNF induced endocannabinoid release and controlled cannabinoid CB1R function in the striatum (De Chiara et al 2010), there is strong co-localization of trkB receptor and CB1R throughout the forebrain (Zhao and Levine 2014). Our results reveal that CB1R may modulate neurotrophic signaling.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that cannabis use can alter levels of BDNF in humans as well as in animals (Jockers-Scherübl et al 2004;Butovsky et al 2005). Recently, it was reported that BDNF induced endocannabinoid release and controlled cannabinoid CB1R function in the striatum (De Chiara et al 2010), there is strong co-localization of trkB receptor and CB1R throughout the forebrain (Zhao and Levine 2014). Our results reveal that CB1R may modulate neurotrophic signaling.…”
Section: Discussionsupporting
confidence: 57%
“…CB1 receptors are highly expressed in the basal ganglia nuclei, the hippocampus, cerebellum, and neocortex (Herkenham et al 1990;Glass and Felder 1997) and are implicated in attenuating glutamatergic exocitotoxic damage by suppressing the neuronal release of glutamate via inhibition of calcium channels (Gerdeman et al 2002;Marsicano et al 2003;Khaspekov et al 2004;Benito et al 2007). The activation of CB1 receptors reduces glutamate release in the dorsal and ventral striatum [possibly through an interaction with brain-derived neurotrophic factor (de Chiara et al 2010)], thereby modulating neurotransmission in the basal ganglia and mesolimbic reward system (van der Stelt and Di Marzo 2005). Stress-induced anxious behavior has been associated with the loss of CB1 receptor function in the striatum (Rossi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, data from mouse (Butovsky et al 2005) and human (D ' Souza et al 2009) studies suggests that cannabis administration directly affects BDNF levels. Mechanistically, a few studies which investigated the interplay between BDNF and cannabinoid system have shown that BDNF controls brain striatal CB1 function (De Chiara et al 2010), and that the lack of CB1 receptor in mice (Aso et al 2008) or chronic antagonism of CB1 receptors in rats (Beyer et al 2010), induces a decrease in hippocampal BDNF levels and manifestation of abnormal neuropsychiatric behavioural phenotypes. 2013).…”
Section: Discussionmentioning
confidence: 99%